Private Voluntary Health Insurance in Development : Friend or Foe? - Preker, Alexander S.; Sheffler, Richard M.; Preker, Alexander S. (Washington, DC: World Bank, 2012)
This volume presents findings of a World Bank review of the existing and potential role of private voluntary health insurance in low- and middle-income countries and is the third volume in a series of reviews of health care financing. Also, this volume is about managing risk. Not the risk of national or man-made disasters but the risk of illness. The developing world is plagued by many of the historical scourges of poverty: infectious disease, disability, and premature death. As countries pass through demographic and epidemiological transition, they face a new wave of health challenges from chronic diseases and accidents. In this respect, illness has both a predictable and an unpredictable dimension. Contributors to this volume emphasize that the public sector has an important role to play in the health sector, but they demonstrate that the private sector also plays a role in a context in which private spending and delivery of health services often composes 80 percent of total health expenditure. Managing risks in the private sector begins at the household level. Private voluntary health insurance is merely an extension of such nongovernmental ways to deal with the risk of illness and its impoverishing effects in low- and middle-income countries. The authors examine frameworks for analyzing health financing and health insurance. They conclude that most studies are hampered by lack of data on the impact of private voluntary health insurance on broad social goals, such as financial protection. They find no overall consensus on the impact of voluntary health insurance on public health activities or on the quality, innovation, and efficiency of personal health services.